FRI0116 Epidemiology and hospitalization rate of rheumatoid arthritis patients in real world setting in italy. (23rd January 2014) - Rossini, M.; Caimmi, C.; Bernardi, D.; Rossi, E.; Viapiana, O.; De Rosa, M.; Adami, S.
Abstract : Background: The epidemiology of most rheumatic diseases is generally esteemed from a sample population and from spontaneous reports. Objectives: Aim of this study was to explore the epidemiology and hospitalization rate of rheumatoid arthritis (RA) patients in real world setting in Italy. Methods: The ARNO Observatory is an Italian population-based patient-centric system with data obtained through record linkage of 11 million inhabitants. This study pertains to a sub-cohort of 5.821.337 people counted in September 2011. The code for the diagnosis of RA is distinct from that of undifferentiated arthritis or psoriatic arthritis. Results: It was present in 21883 subjects with a prevalence of 0.37%. However, among these subjects those who had at least one specific prescription (corticosteroids and/or a DMARDs) during the previous year were 15082 with a prevalence of only 0.23% of "active RA". The prevalence was 0.09% for people aged <39 yrs and it rose progressively to 1.27% on the eighth decade of life and then it fell to 0.79% for elderly aged > 79 yrs. Overall women accounted for 77% of the RA patients, but the female to male ratio was 3.59 for people aged <39 yrs and it progressively decreased to 2.02 for those aged > 79 yrs. (P<0.001 for all mentioned gender differences). The gender differences were even greater for data adjusted for mortality rate. The yearly incidence was 0.038% in females and 0.013% in males. In both gender the incidence rose with age with a peak incidence on the 7 th decade of life and then it gradually decreased for people aged > 69 yrs. The female/male ratio was 8 in people aged <39 yrs but it progressively decreased to 1.3 in those aged > 79. The hospitalization rate in 2011 was 13.5% of RA patients due mainly to cardiovascular diseases. As compared with the general population the hospitalization rate was considerably higher for a number of diseases: cardiovascular diseases 8.65 folds, acute myocardial infarction 3.1 folds, pulmonary diseases 2.0 folds, ictus and TIA 0.8 folds. Conclusions: In this population based data system the prevalence of patients diagnosed as affected by RA in Italy is 0.37% and then close to that reported from previous sample surveys. However, the prevalence of patients also on treatment with corticosteroids or DMARDs is only 0.23%. The female/male ratio decreases with advancing age. The yearly incidence increases up to the 7 th decade of life in both genders and then it slowly decreases. These results indicate that the incidence of active RA is somewhat lower than that previously assumed and that the peak age onset is higher than hitherto assumed. Possibly also for this reason the incidence of hospitalization for cardiovascular diseases is impressively 8 folds higher in active RA patients as compared with the general population. Disclosure of Interest: None Declared